A Novel Railgun Simulation Model Based on a Quasistatic - Gómez de León, Fermín; Repetto, Maurizio; Bissal, Ara (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
This paper presents a novel railgun simulation model based on a quasistatic study in COMSOL. Traditional analytical models are inaccurate as they use the coenergy principle to calculate the force on the armature, yielding the total force in the displacement axis. By using a numerical magnetic solution, a parametric analysis evaluates the flux linkage, armature force, and system resistance at various positions and currents. After characterizing the railgun, the transient problem is solved by coupling the parametric study results with the system's equivalent circuit. Finally, the results are compared with those from the analytical approach.